2017
DOI: 10.1021/jacs.6b11373
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Probes of Capture and Decomposition of Chemical Warfare Agent Simulants by Zr-Based Metal Organic Frameworks

Abstract: New materials for the rapid decomposition of chemical warfare agents (CWAs) are in high demand for protecting military and civilian populations from these weapons of mass destruction. The need for novel sorbents and decontamination catalysts has gained great urgency as terrorists groups demonstrate the ability to synthesize and deploy agents in chemical attacks. Although many new materials, such as metal-organic frameworks (MOFs), have been proposed to use as CWA filtration media, their eventual transition req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
198
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(214 citation statements)
references
References 36 publications
12
198
2
2
Order By: Relevance
“…In addition to the promising activity demonstrated by UiO‐66 and its amino functionalized derivative, we have also shown that using UiO‐67 (Figure ), a MOF which is isostructural to UiO‐66 but contains 4,4′‐biphenyldicarboxylic acid linkers and larger pores, results in a further enhancement in hydrolysis reaction rate compared to UiO‐66 (Figure and Table ) . This reaction rate enhancement is to be expected given that diffusion of the simulant DMNP in UiO‐67 is expected to be faster compared to that in UiO‐66 . Since primary amines have been shown to have a favorable effect on DMNP hydrolysis and the apertures of UiO‐67 are known to promote DMNP diffusion, the next step was to test the activity of amine functionalized UiO‐67 against DMNP.…”
Section: Figurementioning
confidence: 72%
“…In addition to the promising activity demonstrated by UiO‐66 and its amino functionalized derivative, we have also shown that using UiO‐67 (Figure ), a MOF which is isostructural to UiO‐66 but contains 4,4′‐biphenyldicarboxylic acid linkers and larger pores, results in a further enhancement in hydrolysis reaction rate compared to UiO‐66 (Figure and Table ) . This reaction rate enhancement is to be expected given that diffusion of the simulant DMNP in UiO‐67 is expected to be faster compared to that in UiO‐66 . Since primary amines have been shown to have a favorable effect on DMNP hydrolysis and the apertures of UiO‐67 are known to promote DMNP diffusion, the next step was to test the activity of amine functionalized UiO‐67 against DMNP.…”
Section: Figurementioning
confidence: 72%
“…Sometimes, using actual agents can reveal additional mechanisms not observed with simulants . For example, dimethyl methylphosphonate (DMMP) is commonly used as a simulant for GB because it exhibits similar adsorption behavior. However, it does not contain the P−F bond that is broken during sarin hydrolysis, and is therefore not as effective for mimicking reactivity .…”
Section: Introductionmentioning
confidence: 99%
“…[13] Among the linker-appended functional groups screened, primary amine bearing MOFs have shown unprecedented activity in the hydrolysis of DMNP.W eh ave demonstrated that, while keeping other factors constant, installing aprimary amine group on the benzene-1,4-dicarboxylic acid (BDC) linkers of UiO-66 ( Figure 1) can accelerate the catalytic hydrolysis of DMNP by 20 times compared to the parent UiO-66 ( Figure 2a nd Table 1). [14] Since primary amines have been shown to have af avorable effect on DMNP hydrolysis and the apertures of UiO-67 are known to promote DMNP diffusion, the next step was to test the activity of amine functionalized UiO-67 against DMNP.I ts hould be noted that we previously tested the activity of UiO-67m-NH 2 for DMNP hydrolysis at ac atalyst loading of 6mol %. [9, 12a] This reaction rate enhancement is to be expected given that diffusion of the simulant DMNP in UiO-67 is expected to be faster compared to that in UiO-66.…”
mentioning
confidence: 99%